Analysis of acceptance behavior and usage of e-wallet applications - Marfuah, Marfuah; Bagaskoro, Diaz Cahyo; Ayuntari, Chivalrind Ghanevi (Proceeding International Conference on Accounting and Finance, 2024)
The purpose of this study is to find out what factors influence the acceptance behavior and use of E-wallet applications. The population of this study is students who use the Gopay and LinkAja applications in the Special Region of Yogyakarta. Using the convinience sampling method , 100 respondents were selected. Based on data analysis using smartPLS, it is concluded that the overall research model has succeeded in showing the existence of factors that influence a person's behavior in receiving and using E-wallet applications. The results showed that the factors of perceived usefulness, (PU) perceived ease of use (PEOU), and attitudes toward usage (ATU) had a significant positive influence on the intention to use the E-wallet application. Intent to use (ITU) has a significant positive influence on the use of E-wallet applications. Supporting factors, namely information security system (SECURITY), also have a significant positive influence on the use of E-wallet applications. The results of this study have contributed to electronic wallet application service provider companies, especially Gopay and LinkAja to improve their services by considering aspects of ease and security in using electronic wallet applications so that the benefits felt by users are increasing which will later encourage intentions and attitudes to use them.